WEAR BEHAVIOR OF INCONEL 925 ALLOY AFTER PLASTIC DEFORMATION - Sezek, Sinan; Kara, Gamze Ispirlioğlu; Bayram, Seda; Aksakal, Bünyamin (ModTech Publishing House, 2023)
For orthopedic implant applications, the two main properties of a biomaterial: chemical reactivity and mechanical strength, are of great importance. Therefore, metallic biomaterials have a high utilization rate due to their superior mechanical properties. Inconel 925, a metallic alloy, is widely used in the aerospace and automotive industries, nuclear power plants, gas turbines, etc., where high-temperature strength and oxidation resistance are required. To increase its widespread use in the field of health (such as orthopedic implants, medical devices, and surgical instruments). It is aimed at improving the microstructure and mechanical properties of Inconel 925 alloy. For this purpose, 30%, 50%, and 70% deformation hardening were applied to the alloys through extreme plastic deformation. Microstructural changes such as phase transformations, grain boundaries, and size were investigated by characterization methods. The mechanical properties of the alloy were investigated by micro-hardness and wear tests. A very fine-grained microstructure with a grain size of 0.08µm was obtained for Inconel 925 alloy. The hardness of the alloy was increased by 69% with 339 HV. The best wear resistance was obtained in the 70% deformed sample with 0.548µ. © 2023, ModTech Publishing House. All rights reserved.
Keywords: biomaterial; inconel 925 alloy; plastic deformation; rolling; wear